AGAMOUS-LIKE FLOWER regulates flower and compound leaf development through different regulatory mechanisms in Medicago truncatula - Zhang, Juanjuan (Plant Signal Behav, 2019)
We have recently reported that AGAMOUS-LIKE FLOWER (AGLF) identifies the floral organ through regulating class C-function in Medicago truncatula. Here, we show that AGLF is not only involved in flower development but also the compound leaf formation. The aglf mutant exhibits the clustered leaflets, suggesting a trend towards the decreased leaf complexity. Similarly, the ortholog of LEAFY in M. truncatula, SINGLE LEAFLET1 (SGL1), also plays critical roles in both flower and compound leaf development. However, the mutants of the ABC model genes downstream of AGLF and SGL1 display the normal leaves. These data suggest that AGLF and SGL1 regulate floral organ identity through ABC model, but are probably involved in other pathways to control compound leaf development.